Stress Management Strategies to Reduce Academic Stress in Modern Islamic Boarding School Students - Triyuliasari, Anisah; Ni'matuzahroh; Anwar, Zainul (Al-Hayat: Journal of Islamic Education, 2025)
The phenomenon of academic stress among students of modern Islamic boarding schools is increasingly worrying along with high academic and non-academic demands. This study aims to reduce academic stress through interventions in the form of psychoeducation and stress management strategy training for new students at the Darul Hikmah Modern Islamic Boarding School. The research method uses a quantitative approach with a pre-test and post-test design for the same group. This study involved 31 students as samples taken using incidental sampling techniques. The instrument used was the Educational Stress Scale for Adolescents (ESSA) with a reliability of 0.808 which has been adapted into Indonesian. The intervention given in this study was stress management psychoeducation. The data analysis method used was the Wilcoxon test. The results showed that the stress management strategy with the TALK method (Find, Teach, Exercise, Consultation) was proven to be effective. There was a significant increase in students' understanding of academic stress after participating in psychoeducation. In addition, the results also show that the intervention given is able to reduce students' academic stress with a value of (Z = - 3.924 with p = 0.00; Mean Pre-test = 47.00 with Mean Post Test = 41.77) which means that the stress management strategies taught are effective in reducing the pressure experienced by students. This study concludes that psychoeducation and stress management training are effective preventive and curative strategies for dealing with academic stress in the Islamic boarding school environment. The existence of ongoing training and social support from the environment is very much needed to support the sustainability of the intervention results and maintain individual welfare so that students can achieve more optimal academic achievement.